Relevance and actionable mutational spectrum in oral squamous cell carcinoma. (3rd January 2020) - Jayaprakash, Chinchu; Varghese, Vinay Koshy; Jayaram, Pradyumna; Chakrabarty, Sanjiban; Kudva, Adarsh; Ray, Satadru; Satyamoorthy, Kapaettu
Abstract: Background: Screening for lesions in the oral cavity is critical for early diagnosis of oral squamous cell carcinoma (OSCC). Targeted next generation sequencing‐based (NGS) mutation analysis of cancer driver genes becomes a reality for personalized medicine and cancer therapeutics. Materials and methods: In the present study, we have performed a targeted NGS‐based mutation analysis of 50 known oncogenes and tumor suppressor genes in clinically diagnosed potentially malignant lesions and tissues of OSCC. NGS‐based analysis of DNA obtained from biopsies of histopathologically confirmed cases of potentially malignant lesions and OSCC specimens were performed using Ion AmpliSeq™ Cancer Hotspot Panel V2 using the Ion Proton™ Sequencer System, followed by data analysis using Ion Reporter™ and Torrent Suite™ software. Results: NGS analysis indicated a total of 69 mutations present in 25 genes in potentially malignant lesions and OSCC specimens. We identified recurrent mutations in known OSCC driver genes ATM (11%), TP53 (55%), HRAS (16%), SMAD4 (13%), PIK3CA (16%), and ERBB4 (11%) in potentially malignant lesions and OSCC specimens. Driver mutation analysis identified recurrent TP53 and HRAS driver mutations in our OSCC specimens. Conclusion: Data generated from our study may enable an application of targeted NGS analysis of driver mutations for better therapeutic choice and improved outcomes for OSCC subjects when combined with clinical diagnosis.